Re-submission of construction schedule for the next three month (July-September 2019) based on actual work progress - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the re-submission of construction schedule for the next three month (July-September 2019) based on actual work progress of BRACU new campus project site.